2016
DOI: 10.1146/annurev-pharmtox-010715-103042
|View full text |Cite
|
Sign up to set email alerts
|

The Emerging Role of Spinal Dynorphin in Chronic Pain: A Therapeutic Perspective

Abstract: Notable findings point to the significance of the dynorphin peptide neurotransmitter in chronic pain. Spinal dynorphin neuropeptide levels are elevated during development of chronic pain. Importantly, knockout of the dynorphin gene prevents development of chronic pain in mice, but acute nociception is unaffected. Intrathecal (IT) administration of opioid and non-opioid dynorphin peptides initiate allodynia through a non-opioid receptor mechanism; furthermore, anti-dynorphin antibodies administered by the IT ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
39
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 148 publications
(202 reference statements)
1
39
0
Order By: Relevance
“…Altogether, these results suggest that during the period of neuropathy development after PSNL PL265 could sufficiently protect enkephalins to maintain their concentrations at a level capable to stimulate the enkephalinergic system triggering subsequent long adaptive changes (Podvin et al, 2016). This stimulation would be strong enough to significantly alleviate symptoms of neuropathic pain in mice, even after interruption of PL265 administration.…”
Section: Chronic Pain When Initiated and Maintained By Various Factomentioning
confidence: 81%
“…Altogether, these results suggest that during the period of neuropathy development after PSNL PL265 could sufficiently protect enkephalins to maintain their concentrations at a level capable to stimulate the enkephalinergic system triggering subsequent long adaptive changes (Podvin et al, 2016). This stimulation would be strong enough to significantly alleviate symptoms of neuropathic pain in mice, even after interruption of PL265 administration.…”
Section: Chronic Pain When Initiated and Maintained By Various Factomentioning
confidence: 81%
“…Dynorphinergic system involvement in neuropathic pain has mainly been investigated at spinal level, 10,18,46 lates the pain control descending system. 29 Thus, our results indicate that after peripheral nerve injury Pdyn mRNA alterations, so far mainly reported at spinal level, 11,47,48 also occur in the cortical regions.…”
Section: Discussionmentioning
confidence: 99%
“…However, at post-SNL day 10 only, the Pdyn KO animals showed a return to nociceptive baseline values, suggesting that dynorphin could play a pronociceptive role through the maintenance of central sensitization. 18 In fact, when injected at relatively low doses, dynorphin exhibits antinociceptive properties mediated by κ-opioid receptor activation. 16,17 These different roles exerted by dynorphin (ie, pronociceptive and antinociceptive) can be mediated through opioid and non-opioid spinal mechanisms.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although some studies have shown a pronociceptive effect of dynorphin signaling evidence suggests that this is through a non-opioid receptor mediated mechanism (for review see, (Podvin, Yaksh, & Hook, 2016)). The contribution of KORs on specific neuron types or in different regions of the pain pathway and how each might contribute to mediating distinct modalities of pain is less clear.…”
Section: Preclinical Evidence For Kor Involvement In Analgesiamentioning
confidence: 99%